Temperature-dependent electrorheology of a suspension based on copolymeric P(NIPAM-co-[AMIm]Cl) colloidal particles. (16th November 2020) - Pan, Jun Liang; Jin, Xiao; Zhang, Zhenlin; Wang, Li-Min; Liu, Ying Dan; Choi, Hyoung Jin
Abstract: A imidazolium-based poly (ionic liquid), poly(1-allyl-3-methyl imidazolium chloride) (P[AMIm]Cl) was combined with the temperature-sensitive polymer poly(N-isopropylacrylamide) (PNIPAM) via random copolymerisation of the monomers [AMIm]Cl and NIPAM. The synthesised copolymer was characterised by nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscope (SEM). Then its stimuli-responsive properties were studied at different electric field strengths and temperatures when it was dispersed in silicone oil. It was found that the colloidal copolymer particles were electro-responsive, showing excellent electrorheological (ER) effect. It was interesting that the ER effect of the copolymer was temperature-dependent. As the temperature increased from 5 °C to 50 °C, the dynamic yield stress of the suspension was found to increase with temperature. The temperature dependence of both yield stress and current density became stronger as the temperature was higher than 30 °C. The significant temperature-dependence of the suspension was attributed to the PNIPAM segment in the copolymer which could be swelled by silicone oil at higher temperature.